Mittelalterliche Lyrik im Kontext - Kellner, Beate; Rudolph, Alexander (Deutsche Literatur, 2024)
The anthology, which is the result of an interdisciplinary conference in Munich, looks at medieval lyric poetry from a European perspective. It examines the points of contact, as well as differences, between the poetry of different vernacular languages in the spectrum of genres and makes references to ancient poetry as well as to the Song of Songs. It also sees itself as a contribution to a historicization of lyric theory